2020
DOI: 10.1002/advs.202000704
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxins Bind to the Cell Surface of Unculturable Acinetobacter baumannii and Cause Unique Dependent Resistance

Abstract: Multidrug‐resistant Acinetobacter baumannii is a top‐priority pathogen globally and polymyxins are a last‐line therapy. Polymyxin dependence in A. baumannii (i.e., nonculturable on agar without polymyxins) is a unique and highly‐resistant phenotype with a significant potential to cause treatment failure in patients. The present study discovers that a polymyxin‐dependent A. baumannii strain possesses mutations in both lpxC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 54 publications
0
67
0
Order By: Relevance
“…Unlike previous simulation studies in which the bacterial OM was simplified into a symmetric or asymmetric LPS bilayer with model phospholipid compositions, [23][24][25][26] we utilized the quantitative membrane lipidomics results from polymyxinresistant A. baumannii 5075R to construct a more realistic OM model that allowed for better precision when characterizing interactions with the octapeptins. 19 Analysis of the simulations revealed that a minor structural variation between octapeptin C4 and FADDI-115, namely, the presence of a hydroxyl group on the fatty acyl group of octapeptin C4 (Fig 1A), was sufficient to impact their conformational transitions and resulted in different free energy profiles for OM penetration. These results provided novel atomic-scale insights into the structure-activity relationship of the octapeptins against polymyxin-resistant Gramnegative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous simulation studies in which the bacterial OM was simplified into a symmetric or asymmetric LPS bilayer with model phospholipid compositions, [23][24][25][26] we utilized the quantitative membrane lipidomics results from polymyxinresistant A. baumannii 5075R to construct a more realistic OM model that allowed for better precision when characterizing interactions with the octapeptins. 19 Analysis of the simulations revealed that a minor structural variation between octapeptin C4 and FADDI-115, namely, the presence of a hydroxyl group on the fatty acyl group of octapeptin C4 (Fig 1A), was sufficient to impact their conformational transitions and resulted in different free energy profiles for OM penetration. These results provided novel atomic-scale insights into the structure-activity relationship of the octapeptins against polymyxin-resistant Gramnegative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…33 Notably, the accurate lipid composition of the OM (Fig 1B) was based on our quantitative lipidomics results of polymyxin-resistant A. baumannii 5075R. 19 Initially, the octapeptin molecules were placed above the outer leaflet of the OM using the gmx insert-molecules tool by replacing the overlapping water molecules. 34 TIP3P water molecules and counter-ions (CaCl2) were employed to hydrate and neutralize the simulation systems, respectively.…”
Section: System Preparationmentioning
confidence: 99%
“…Pairwise sequence alignment with Stretcher (EMBL-EBI) [ 45 ] disclosed 100% identity of the VgrG- and Hcp-encoding contigs from Ab-S and Ab-D. According to Zhu et al, mutations in katG , encoding a catalase involved in reactive oxygen species scavenging, affected polymyxin dependence in MRD A. baumannii AB5075 [ 15 ] and inactivation of mrcA , encoding the penicillin-binding protein A1, has been suggested to promote LOS loss [ 7 ]. Nevertheless, no mutations/substitutions/insertions in katG or mrcA were present in Ab-S and Ab-D.…”
Section: Resultsmentioning
confidence: 99%
“…This was discovered, however, in colistin-resistant A. baumannii obtained after 120 generations of passaging on 10 µg/mL polymyxin B, while we observed the emergence of phenotypically colistin-dependent subpopulation already after 8 passages on colistin [ 38 ]. Recently, a transcriptomic analysis of a colistin-dependent isolate in relation to its parent colistin-susceptible MRD A. baumannii AB5075 revealed 1.7-fold increased expression of mlaD and 2.0-fold decreased expression of pldA in colistin-dependent bacteria [ 15 ]. We believe that this discrepancy can be attributed to the difference between strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation